Serviço Social, teoria social de Marx e a direção política da profissão - Salvador, Mariléa Borges de Lima (2018)
The thesis investigates the relation between the Social Service and Marx's social theory, seeking to know the political direction the profession has taken to consolidate the Critical Social Service, from the approach with the Marxist tradition without the Marxian thought until the encounter with the work of Marx. Starting from the hypothesis that the Social Service has its genesis in the conservative politics of the capitalist State, that such conservatism expresses the reformist political direction advocated by that State as a protector and maintainer organ of the interests of the capitalist class, and that the conservative / reformist character of the profession persists to the present day challenging the profession political nature interventionist character committed to a professional exercise immersed in the critique of political economy, in the understanding of social service as a profession inserted in the socio-technical division of labor and sustained by the ethical principle of the intransigent defense of the interests of working class, the thesis is the result of a bibliographical research with the effective instrumental of the investigative process execution defined by the systematic study of the literature concerning the question of the relation established between the Social Service and Marx's social theory conveyed in the written and spoken works disseminated with their theoretical contributions in books, websites, videos and backed by the historical and theoretical foundations of the profession explained by the Marxist critical theoretical matrix and constituted from the 1960s following the social question and consolidated in the years 1980. The first part of the text discusses the meeting of the Social Service with Marxist thought emphasizing the sociohistorical and ideopolitical antecedents of the social service and social theory of Marx relation occurred in the contexts of the social question produced by the capitalist social reproduction in Europe, Latin America and Brazil. In the second debate the construction of the Critical Social Service with the Marxist critical theoretical matrix and the conception of the Social Service as an institutionalized profession oriented by the movement of rupture intention that the profession agreed to carry out as a way to suppress the traditional and conservative bias in which the profession was based. The third part deals with the limitations, contradictions and possibilities in the political direction of critical social service on the way to the emancipation of the working class